Computational thermodynamics and informational technologies in the field of computer design of materials - Udovsky A.L. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Computational thermodynamics and informational technologies in the field of computer desing of materials as well as appliance of CALPHAD method on resolution of thermodynamic problems are presented in this paper.